A recent review on 2019 novel coronavirus outbreak - Shaji, Bipin; Suresh, Abisri; Vasanth, Nimitha; Stanly, Sharon Mary (International Journal of Basic & Clinical Pharmacology, 2020)
SARS-CoV2, a single-stranded RNA virus that can cause a wide array of clinical manifestations ranging from mild to severe (respiratory failure). The spread of SARS-CoV2 has now become uncontrollable leading to a pandemic. The infection is usually transmitting through cough droplets and sneeze. The main clinical manifestations of the disease are similar to common respiratory tract infections and may become fatal after the development of symptoms such as severe dyspnea, low PaO2/FiO2 (fraction of inspired oxygen) ratio, and severe decline in blood oxygen saturation. Current diagnostic tools employed at the moment include time-consuming NAAT (nucleic acid amplification test). Recent investigations and researches are aimed at rapid serological testing. Real-time reverse transcription-polymerase chain reaction (rRT- PCR) is the standard method of testing, using respiratory samples obtained by the nasopharyngeal swab. Medications such as darunavir, ribavirin, remdesivir, interferon, and lopinavir/ritonavir combination therapy were used for the management of the infection. Social distancing, use of protective masks, isolation of the infected persons and maintaining personal hygiene helps in the prevention of the disease.